غرس القيم الأخلاقية المتعلقة بادآب التعامل عبر وسائل التواصل الاجتماعي في نفوس الأجيال الشابة وسلوكياتهم: Instilling Ethical Values Related to Etiquette on Social Media in Younger Generation & Their Behaviours - Alharasi, Raqiya Abdallah Nasser; Musal Kassim, Sayyid Buhar (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
As social media becomes increasingly prevalent in our daily lives, it is important to ensure that young people are equipped with the necessary ethical values to navigate these virtual spaces. This is especially true given the many potential pitfalls and negative impacts that can arise from the use of social media, such as cyberbullying, online harassment, and the spread of misinformation. Teaching children or young people the values and methods to deal correctly with social media interactions became of a great important for their wellbeing and achieving well in their lives. This may help them to avoid the negative impacts of such interactions on their minds, emotions, and behaviours in daily life. There are many values to be taught in this regard and this paper is a try to investigate in this matter to recognize and crystalize these values and the ways to inculcate them in the selves of young generations.